Chinese Reading Proficiency Guidelines: A Case Study of Chulalongkorn University Students - Ek-atchariya, Sansanee (Journal of Sinology (วารสารจีนวิทยา), 2007)
This research is to study and propose Chinese reading proficiency guidelines for Thai students using Chulalongkorn University (CU) Chinese-majored students as a case in focus. In our analysis of each course in the curriculum of CU Chinese Language Major , we first apply the so - called Language Functional Trisection , as developed by ACTFL CPG to help classify different levels of reading proficiency. Next we compare ACTFL Chinese reading proficiency guidelines to those of CU. Our finding shows that in all levels not only is the reading ability of CU students majoring in Chinese higher than that of ACTFL's, their level of progression grows faster than that of ACTFL's as well.